2006
DOI: 10.1111/j.1600-0714.2006.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional (−1171 5A→6A) polymorphisms of matrix metalloproteinase 3 gene as a risk factor for oral submucous fibrosis among male areca users

Abstract: The results indicated that the 5A genotype of MMP3 promoter was associated with the risk of OSF but not OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Relative to heterozygotes, individuals homozygous for 5A have increased MMP3 gene expression and individuals homozygous for 6A have decreased gene expression (174). The 6A genotype has been correlated with increased risk for coronary disease and progression of atherosclerosis (312), oral submucosal fibrosis (277), and celiac disease in men (179). For MMP8, an association between a minor allele haplotype and preterm premature rupture of membranes has been identified (289).…”
Section: B Mmp Polymorphismsmentioning
confidence: 99%
“…Relative to heterozygotes, individuals homozygous for 5A have increased MMP3 gene expression and individuals homozygous for 6A have decreased gene expression (174). The 6A genotype has been correlated with increased risk for coronary disease and progression of atherosclerosis (312), oral submucosal fibrosis (277), and celiac disease in men (179). For MMP8, an association between a minor allele haplotype and preterm premature rupture of membranes has been identified (289).…”
Section: B Mmp Polymorphismsmentioning
confidence: 99%
“…Chaudhary and colleagues in their study found that the 5A allele might play an important role in the susceptibility to HNC, as individuals with 5A/5A genotype had nearly two fold risk of HNSCC (OR = 1.94) when compared to controls [28]. However, Tu and colleagues found that the 5A/5A genotype was associated with the risk of oral submucous fibrosis but not OSCC [9].…”
Section: Discussionmentioning
confidence: 93%
“…The study also concluded that the genotypic linkage among the collagen-related genes, MMPs, TIMPs, and cytokines related to OSF formation requires more information to specify the risk of OSF in areca chewers [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations